Membangun Generasi Berkarakter melalui Pendekatan Pembelajaran IPS - Chairunisa Mardiah Ramadhani; Sifana Alqorana; Yuma Laberty Ibadi; Sani Safitri (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Using an integrated approach to education, social studies learning is essential to producing a generation with character. This method not only aims to acquire academic knowledge, but also to instil character principles that are important in everyday life. Students gain an understanding of principles such as justice and democracy through social studies learning, which are highly relevant in the context of social society. Character education and social context are linked to improve students' critical thinking skills. One of the goals of the social studies curriculum transformation is for students to internalise the principles taught into their daily lives. Social studies learning can be useful for building strong character for the younger generation to face future challenges.